Distributive Justice and Richard Susskind’s Online Courts in the Brazilian Judicial System: an analysis of the Justice 4.0 Program - Santos Divino, Sthéfano Bruno (Pontificia Universidad Católica del Perú, 2024)
Richard Susskind’s Online Court is no longer just an ideal, but a policy for implementing and developing the judiciary alongside technology. Its application in the Brazilian legal system has been proposed, applied, improved, and constantly refined by the National Council of Justice. The aim is to understand the structuring legal concept of the Virtual Court, created by Richard Susskind, to identify its premises, foundations, and pretensions. It then shows how Susskind’s Virtual Court has been applied in the Brazilian legal system through the Justice 4.0 program. Finally, the current policies are briefly analyzed to verify their compatibility with due process of law. Thus, the research problem that guides this article and the proposed objectives can be expressed by the following question: has the Justice 4.0 Program complied with the foundations and fundamental precepts of Richard Susskind’s Virtual Courts, as well the Distributive Justice? The conclusion is that despite technological and legal advances, the Justice 4.0 Program is still precarious in terms of accessibility, transparency, and proportionality of justice. The method used is integrated research combined with bibliographical research.

O Tribunal Virtual de Richard Susskind deixou de ser apenas um conceito para ser uma política de implementação e desenvolvimento do judiciário ao lado da tecnologia. Sua aplicação no sistema jurídico brasileiro foi proposta, aplicada, aprimorada e constantemente aperfeiçoada pelo Conselho Nacional de Justiça. Objetiva-se compreender o conceito jurídico estruturante de Tribunal Virtual, criado por Richard Susskind, para identificar suas premissas, fundamentos e pretensões. Posteriormente, demonstra-se como o Tribunal Virtual de Susskind tem sido aplicado no sistema jurídico brasileiro por meio do Programa Justiça 4.0. Por fim, analisa-se brevemente as políticas em curso para verificar sua compatibilidade com o devido processo legal. Dessa forma, o problema de pesquisa que norteia este artigo e os objetivos propostos podem ser expressos pelo seguinte questionamento: o Programa Justiça 4.0 tem atendido aos fundamentos e aos preceitos fundamentais dos Tribunais Virtuais de Richard Susskind, bem como à Justiça Distributiva? Conclui-se que apesar dos avanços tecnológico e jurídico existentes, o Programa Justiça 4.0 ainda é precário quanto à acessibilidade, a transparência e a proporcionalidade da justiça. O método utilizado é o de pesquisa integrada somado à técnica de pesquisa bibliográfica.
Justiça Distributiva e os Tribunais Virtuais de Richard Susskind no Sistema Judiciário brasileiro: uma análise do Programa Justiça 4.0
Keywords: National Council of Justice; Due process; Justice; Judiciary; Richard Susskind; Online courts; Conselho Nacional de Justiça; Devido processo legal; Justiça; Judiciário; Richard Susskind; Tribunais virtuais; https://purl.org/pe-repo/ocde/ford#5.05.00